«Partnership for Modernization» as an Instrument of Developing the Legal Base of Customs Cooperation between Russia and the EU - D. A. Turlanov (Vestnik MGIMO-Universiteta, 2014)
Russia-EU customs cooperation legal base in force has been outdated and is hardly able to meet demands of trade-economic cooperation between Russia and EU. In particular, structure and substance of Russia-EU customs cooperation regulation do not allow to successfully respond to the challenges of bilateral trade. This is stipulated by legal changes at international level for Russia including ratification of International convention on harmonization and simplification of customs procedures of May 18, 1973, forming of Customs union, WTO accession) and following reforms of custom procedures in Russia. Besides, legal base of Russia-EU customs cooperation does not take into consideration the following measures of modernization of customs regulation in the EU: active use of preliminary information change, electronic methods of fulfilment of customs formalities as well as implementation of modern customs techniques, targeted at simplification and securing of customs formalities. Due to the above-mentioned facts and keeping in mind the high role of mutual trade for well-being of both Russia and EU, improvement of customs cooperation legal base becomes the urgent task. The author of the article points out the Initiative Russia-EU «Partnership for modernization» is able to be one the most crucial instruments of development of Russia-EU customs cooperation legal base. The Initiative is conceived to contribute to economic growth of Russia and EU by virtue of implementation of modernized agenda including in customs sphere. Because of that author analyses customs cooperation issues provided by the Initiative, detects its weak points and proposes approaches towards enhancing Russia-EU trade-economic cooperation by means of modernization of trade flows customs administration.